Penyebab Keterlambatan Pengembalian Berkas Rekam Medis Rawat Inap di Rumah Sakit - Nurmawati, Ida; Rohmah, Amaliya Nikmatul; Alfiansyah, Gamasiano (FORIKES, 2022)
Accuracy in returning medical record files is necessary in order to realize good medical record management, because it influences policy making, management decisions, and the delivery of information to each patient. So a study is needed that aims to study the causes of delays in returning inpatient medical record files at the hospital. This study is a literature review involving 19 articles from Google Scholar and the Garuda Portal. The results of the study stated that the causes of delays in returning medical record files were: 1) man: lack of knowledge regarding the deadline for returning medical record files, training had not been carried out, staff attitude was not good, education level was not appropriate, staff had less years of service; 2) money: budget is not yet available; 3) method: there is no SOP, the SOP has not been socialized, the officers do not work according to the SOP, monitoring has not been carried out; 4) material: incomplete filling of the patient's medical record file; 5) machine: lack of other supporting facilities.Keywords: hospital; late returns; medical records ABSTRAK Ketepatan pengembalian berkas rekam medis diperlukan guna mewujudkan manajemen rekam medis yang baik, karena berpengaruh terhadap pengambilan kebijakan, keputusan manajemen, serta penyampaian informasi kepada setiap pasien. Maka diperlukan studi yang bertujuan untuk mempelajari penyebab keterlambatan pengembalian berkas rekam medis rawat inap di rumah sakit. Studi ini merupakan literature review yang melibatkan 19 artikel dari Google Scholar dan Portal Garuda. Hasil studi menyatakan bahwa penyebab keterlambatan pengembalian berkas rekam medis adalah: 1) man: kurangnya pengetahuan terkait batas waktu pengembalian berkas rekam medis, belum dilakukan pelatihan, kurang baiknya sikap petugas, tingkat pendidikan tidak sesuai, masa kerja petugas kurang; 2) money: belum tersedianya anggaran; 3) method: belum ada SOP, belum disosialisasikannya SOP, petugas tidak bekerja sesuai SOP, belum dilaksanakannya monitoring; 4) material: ketidaklengkapan pengisian berkas rekam medis pasien; 5) machine: kurangnya sarana penunjang lain.Kata kunci: rumah sakit; keterlambatan pengembalian; rekam medis